Peran Badan Usaha Milik Desa dalam Meningkatkan Pendapatan Asli Desa di Desa Tatede Kecamatan Lopok Kabupaten Sumbawa - Donny Wijaya (Jurnal Syntax Admiration, 2023)
This study aims to know the role of village-owned enterprises in increasing Village Own Source Revenue and to know the obstacles in managing village Owned Enterprises of Tatede village. The location and time of study was done in Tatede Village, Lopok sub-district, Sumbawa district from June to August 2023. The type of this study was qualitative descriptive study, namely study that describes several data formulated in the form of words. The method used to collect data is by using observation, interviews and documentation. The data analysis tool used was the theory of Miles and Huberman which consists of data collection, data reduction, data presentation and verification. The results of the study showed that the role of village Owned Enterprises of Tatede village was running properly, such as doing savings and loan business and water deportation, in which from the both of these business can improve the village economy, provided new employment opportunities for village communities and it could increase village owned enterprise. Village owned enterprise of Ai Muncar has been effective in providing contribution on Village Own Source Revenue in Tatede Village. The management of Ai Muncar Village Owned Enterprise had been done using cooperative principles, transparency, which was done professionally and independently.